The impact of adverse reactions to injectable filler substances on quality of life: results from the Berlin Injectable Filler Safety (IFS) – study. (25th February 2016) - Düker, D.; Erdmann, R.; Hartmann, V.; Nast, A.; Rzany, B.; Bachmann, F.
Abstract: Background: Injectable filler substances are commonly used in aesthetic medicine. Adverse reactions are rare, but may cause severe impact on quality of life (QoL). To the best of our knowledge, data on the impact of adverse reactions caused by injectable filler substances on QoL is missing. Objective: To evaluate the impact of adverse filler reactions on the QoL. Material and methods: The Injectable Filler Safety (IFS) – study is a partially population‐based registry for adverse reactions due to injectable filler substances. In 2008, the Dermatology Life Quality Index (DLQI) questionnaire was added to the questionnaires of the IFS study. For this analysis, only patients with a completed DLQI were included in the analysis. Results: One hundred and four patients of the IFS study were analysed. A total of 88.5% were female with an average age of 49.2 years. Here, 50.0% were treated with biodegradable and 40.4% with permanent fillers. The most common adverse reactions were nodule formation and hardening. Most patients experienced mild to moderate adverse reactions. Impact on QoL was moderate with an average of 8.9 (±8.4 SD) in patients with adverse reactions to biodegradable and 10.5 (±9.4 SD) to permanent products. However, 24.0% and 13.4% showed a large or a very large impact on QoL. Conclusion: Adverse reactions to injectable filler products can have a considerable impact on the QoL, comparable to severe chronic inflammatory skin diseases such as psoriasis.